Measuring the Effects of Monetary Policy in the Euro Area: The Role of Anticipated Policy - Florian Höppner; Jan Gottschalk (Kiel Institute of World Economics (IfW), 2001)
This paper investigates within a SVAR framework the effects of anticipated monetary policy in the euro area. Building on a procedure recently proposed by Cochrane which yields the response of output to an anticipated monetary policy impulse, we show that in the past twenty years anticipated monetary policy has had a considerable influence on output. Moreover, we compute the output effects of the systematic monetary policy response to aggregate demand and supply shocks and find that monetary policy pursues a counter-cyclical policy in response to demand shocks and, despite considerable lags, is pro-cyclical with regard to supply shocks.
Keywords: C52; C32; E52; 330; Vector Autoregression; Systematic Monetary Policy; Historical De-composition; Geldpolitik; Schock; Erwartungstheorie; Wirtschaftspolitische Wirkungsanalyse; Konjunktur; Europäische Wirtschafts- und Währungsunion; VAR-Modell; Schätzung; EU-Staaten